Blocked-Dwt Based Vector Image Watermarking - Dincer, Kivanc; Sever, Hayri; Elbasi, Ersin; Senol, Ahmet (Ieee, 2015)
Image watermarking is in use for proving ownership for a fairly long time. For most of the study on this area, a pseudo random number sequence PRSN or a binary image logo is embedded as watermark. Nowadays the owner's face or sound is also embedded as biometric watermark. Image is transferred to discrete wavelet transform domain, watermark is embedded to DWT values, then DWT values are retransformed to spatial domain to obtain watermarked image. Embedding a vector image logo as watermark was not tried in previous works. In this work, non-blind robust watermarking is applied using a vector image as watermark. Various attacks are applied to watermarked images and for each of these attacks vector image watermark is obtained equal or almost equal to the original. Embedding vector image as watermark will bring a new discipline for image watermarking and a new development will arise in this perspective.
Blocked-DWT Based Vector Image Watermarking
Elbasi, Ersin/0000-0002-8603-1435; Sever, Hayri/0000-0002-8261-0675
Keywords: Non-Blind Robust Image Watermaking; Vector Image Watermark; Discrete Wavelet Transform Dwt; Block-Based Dwt